2000
DOI: 10.1364/ol.25.000666
|View full text |Cite
|
Sign up to set email alerts
|

Cavity ringdown spectroscopy using mid-infrared quantum-cascade lasers

Abstract: Cavity ringdown spectra of ammonia at 10 parts in 10(9) by volume (ppbv) and higher concentrations were recorded by use of a 16-mW continuous-wave quantum-casacde distributed-feedback laser at 8.5 mum whose wavelength was continuously temperature tuned over 15 nm. A sensitivity (noise-equivalent absorbance) of 3.4x10(-9) cm(-1) Hz(-1/2) was achieved for ammonia in nitrogen at standard temperature and pressure, which corresponds to a detection limit of 0.25 ppbv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 12 publications
0
59
0
Order By: Relevance
“…46 A sensitivity of 9.7ϫ 10 −11 cm −1 Hz −1/2 , i.e., within an order of magnitude of the ultimate shot-noise-limit, was achieved with the application of QCLs to NICE-OHMS. 47 Focusing on potential field-deployable systems, Silva et al 8 reported a study which combined a thermoelectrically ͑TE͒ cooled pulsed QCL with CRDS and ICOS.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…46 A sensitivity of 9.7ϫ 10 −11 cm −1 Hz −1/2 , i.e., within an order of magnitude of the ultimate shot-noise-limit, was achieved with the application of QCLs to NICE-OHMS. 47 Focusing on potential field-deployable systems, Silva et al 8 reported a study which combined a thermoelectrically ͑TE͒ cooled pulsed QCL with CRDS and ICOS.…”
Section: Introductionmentioning
confidence: 87%
“…IV A 3 and is comparable to several other CEAS or ICOS studies exhibiting a NEA down to 4 ϫ 10 −8 cm −1 Hz −1/2 . 50,52,54,55,58 It is still almost a factor of ϳ50 less sensitive than CRDS employing a cw QCL as demonstrated by Paldus et al, 46 which may be explained by the commonly omitted cavity mode noise in CRDS. For CEAS or ICOS the minimum detectable absorption is typically lim- ited to 10 −2 -10 −3 due to incomplete averaging over the cavity resonances.…”
Section: System Performancementioning
confidence: 99%
“…If mirror reflectivity remains constant during experiments, change in ring-down time can be linked to increased absorption or scattering within the sample placed between the mirrors. CRDS has long been used to measure gas-phase absorbers [1][2][3] or aerosols [4][5][6][7][8] since optical losses due to scattering in the gas phase is minimal [9,10] and effective path lengths of kilometers can be achieved. In addition, since the measurement monitors the rate of light lost from the cell, the measurement is independent of spectroscopic source power fluctuations.…”
Section: Cavity Ring-down Spectroscopy (Crds)mentioning
confidence: 99%
“…Cavity ringdown (CRD) is a sensitive optical spectroscopic technique which was introduced almost 20 years ago and which has been employed in numerous studies in various configurations and applications [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In contrast to conventional optical absorption and transmission techniques, CRD is based on the time measurement of the exponential decay of the light intensity within a cavity formed by highly reflective dielectric mirrors.…”
Section: Cavity Ringdown Spectroscopymentioning
confidence: 99%